1985
DOI: 10.1056/nejm198507043130101
|View full text |Cite
|
Sign up to set email alerts
|

Calcification of Entheses Associated with X-Linked Hypophosphatemic Osteomalacia

Abstract: We undertook a retrospective analysis of 26 patients with X-linked hypophosphatemic osteomalacia (or rickets), whose ages ranged from 1 to 62 years and who were from 11 different kindreds, to determine the prevalence and clinical characteristics of a unique disorder of the entheses (tendons, ligaments, and joint capsules). We found a generalized involvement of the entheses, with exuberant calcification of tendon and ligament insertions and of joint capsules, in 69 per cent of the subjects. The prevalence and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
6

Year Published

1985
1985
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(51 citation statements)
references
References 15 publications
1
43
1
6
Order By: Relevance
“…Lumbar BMDarea and lumbar BMDvolume values of patients were compared with sex-and age-reference values by using those reported by Boot et al (24), which were obtained by the same DXA machinery equipped with the same software as we used. In all patients with X-linked hypophosphatemic rickets radial BMD by single-photon absorptiometry instead of lumbar BMD was measured because they usually have reduced appendicular BMD independent of treatment (25)(26)(27) and increased axial BMD (26,27) caused by overabundance of partially mineralized osteoid (26), or a high prevalence of spinal osteosclerosis and enthesopathy (27,28). The radial BMD values were compared with sex-and age-reference values by using our own normative data (29).…”
Section: Patientsmentioning
confidence: 99%
“…Lumbar BMDarea and lumbar BMDvolume values of patients were compared with sex-and age-reference values by using those reported by Boot et al (24), which were obtained by the same DXA machinery equipped with the same software as we used. In all patients with X-linked hypophosphatemic rickets radial BMD by single-photon absorptiometry instead of lumbar BMD was measured because they usually have reduced appendicular BMD independent of treatment (25)(26)(27) and increased axial BMD (26,27) caused by overabundance of partially mineralized osteoid (26), or a high prevalence of spinal osteosclerosis and enthesopathy (27,28). The radial BMD values were compared with sex-and age-reference values by using our own normative data (29).…”
Section: Patientsmentioning
confidence: 99%
“…It is not related to the severity of the biochemical changes, which in this case were so minimal that the diagnosis could not have been established without the family history; nor is it associated with the presence of osteomalacia or its treatment (Polisson et al 1985). The enthesopathy may be entirely symptomless, as in this case, but may contribute to the high incidence of arthrosis which has been noted in XLH (Hardy et al 1989).…”
Section: Discussionmentioning
confidence: 76%
“…In a study of 26 patients Polisson et al (1985) found two thirds to be affected, the incidence increasing with age from none under the age of 10 to 100 percent in the over-forties. A similar incidence was found by Hardy et al (1989) who found that women had a slightly higher incidence than men.…”
Section: Discussionmentioning
confidence: 98%
“…This is most notable at the sacroiliac joints, where widening or fusion may suggest early-or late-stage inflammatory sacroiliitis (1 1). Subchondral bone erosions, however, are not observed (9). In the spine, osteopenia is not prevalent, and the classic "rugger jersey" finding most characteristically seen in renal osteodystrophy is an uncommon radiographic feature (12).…”
Section: Discussionmentioning
confidence: 99%